PENGARUH BUDAYA KLAN TERHADAP KETERIKATAN KERJA PADA GENERASI MILENIAL DENGAN KEPEMILIKAN PSIKOLOGIS SEBAGAI MEDIATOR - Viona Wijaya; Jimmy Ellya Kurniawan (JURNAL ILMIAH EDUNOMIKA, 2024)
Millennials (22 – 42 years old) are beginning to dominate the world of work and fill in important positions on various companies in 10 – 15 years to come, making them an important asset for Indonesia especially in the demographic bonus period. However, a high number of turnover cases and the lack of work engagement in Millennials can potentially be a disadvantage for companies as well as the national economic growth of Indonesia. One of the external factors proved to effect work engagement is organizational culture, especially clan culture. The purpose of this study is to understand how psychological ownership as internal factor can mediate the effect of clan culture towards work engagement in Millennials. This is a quantitative and correlational research, which involves data collection using questionnaire to 275 respondents. Data analysis technique used for mediation data is causal steps and Sobel test. The result shows a significant effect of clan culture towards work engagement in Millennials with psychological ownership as mediator, be it direct (ß=0.805, p